NURSES’ PERFORMANCE REGARDING VENTILATOR’S ALARMS IN CRITICAL CARE UNITS AT KHARTOUM PUBLIC HOSPITALS (2021) - Mohammed Ibrahim, Mahmoud; Abdallah Awad, Higazi Mohammed Ahmed; ELHassen Mukhtar , Hanadi Mohammed (International Journal of Research -GRANTHAALAYAH, 2023)
Ventilation alarms in critical areas are widely used, which is an important part of many machines in particular (MV) as it alerts nurses to changes in accordance with patient conditions. Therefore, nurses should be aware of the function and limitations of ventilation modes and alarm management 1. Purpose: This study aims to study nurses’ procedures regarding Ventilator alarms in critical care units. Method: This was a descriptive study based on various hospitals conducted at major public hospitals in Khartoum Province. Includes (100) Nurses working in critical Care units. The data was collected by Observational Checklist on nurse performance in parts and alarms and was analyzed using a computer statistics program for the community program. Results: The study showed that the participants’ complete procedures were satisfactory and that there was an important relationship between the participant’s suitability and their ability to manage the ventilation machine. Conclusion: The total number of research team practices was 58.0% with a score of 1.58 ± (.496). Despite their satisfactory performance and may be due to the disclosure of their college experience or the length of their time in the program.so research Recommend, verifying skin tones for nursing staff at regular intervals based on evidence related to the ventilation machine. habits, it is important to do research to know those processes.